CO-OP RESOURCES THAT LEAD TO SUSTAINABLE COMPETITIVE ADVANTAGE - Magnus Machado, Mirian; Oliveira Henkels, Daniela; Dalfovo, Michael Samir; Gonçalves, Andressa (REBRAE, 2017)
This study aims to analyze the organizational resources to assist the co-op to achieve sustainable competitive advantage. The unit of analysis in this study, the co-op itself, has been showing on the market, its growth last year was more than 30%, reaching the second place in its segment on a national level. From this market segmentation are used various resources, as well as physical, human and organizational. The theory of research based view on resources and VRIO model provided the theoretical basis for this study. The research was used characterized with descriptive and objective quantitative method, and data collection via survey and secondary sources. As an instrument of collection, a questionnaire was used; which has been already validated by other theoretical studies. The questionnaire was applied with tactical and strategic-level managers of the co-op, whereas a total of 152 answers respecting a sampling error of approximately 6%. For analysis of the primary data statistic was used: relative frequency, average, standard deviation, Pearson correlation and factor analysis. The main results obtained for a sustainable competitive advantage are physical capital resources with greater perception of influence. The feature of organizational capital was considered of minor influence to the achievement of competitive advantage. However, it is noteworthy that the major averages highlight the items: ethics and respect to Member (physical Capital resource), the mark of the co-op (feature of Organizational Capital), the training offered by co-op and the benefits offered by the cooperative (Human Capital resource). This work helps the perception of managers who experience the daily life of the co-op, in relation to available resources, highlighting the points to be worked out and that today are a source of competitive advantage. Therefore, enabling new research as well as relating to organizational resources.